2018
DOI: 10.1136/tobaccocontrol-2018-054560
|View full text |Cite
|
Sign up to set email alerts
|

Heated tobacco product regulation under US law and the FCTC

Abstract: Tobacco companies are marketing new ‘heated tobacco products’ (HTPs) composed of battery-powered holders, chargers and tobacco plugs or sticks. The non-tobacco HTP components have escaped effective regulation under many countries’ tobacco control laws because they are packaged and sold separately from the tobacco-containing components. In the USA, HTPs cannot be marketed unless the Food and Drug Administration determines that allowing their sale would be ‘appropriate for the protection of the public health’. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The heated tobacco smoking technology has become increasingly popular [6,79]. The most popular HTP product -IQOS from PMI -is widely available in 33 countries worldwide, including 21 European countries [93].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The heated tobacco smoking technology has become increasingly popular [6,79]. The most popular HTP product -IQOS from PMI -is widely available in 33 countries worldwide, including 21 European countries [93].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of them IJOMEH 2019;32(5) 67% male), 3 consecutive measurement days after being overnight smoking abstinent; 3 different products: a conventional cigarette, an e-cigarette, IQOS; during each session 1 product was used for 5 min; the exhaled CO measurements and dedicated questionnaires were administered throughout each session -cigarette smoking for 5 min resulted in a significant increase in the exhaled CO, whereas using IQOS resulted in a small but reliable increase (0.3 ppm) -cigarette craving was reduced significantly after the product use, with the decline being stronger for tobacco smoking than for e-cigarettes or IQOS a short-term use of IQOS can be effective to momentarily reduce the acute cigarette craving and withdrawal symptoms -IQOS is more popular with novice users than an e-cigarette Independent studies performed with the aim of assessing the health impact of HTP use are very limited (Table 3). Adriaens et al showed that 5 min of IQOS use resulted in a small but reliable increase (0.3 ppm) in the exhaled CO level [79].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, IQOS and other HTPs should not be permitted to be marketed with labelling or advertising that claims or implies modified exposure because the PMI’s own studies demonstrate that consumers perceive reduced exposure claims as reduced risk claims. Both US law (FSPTCA, 911(g) and 903) 10 and the Framework Convention on Tobacco Control 38 (FCTC) and FCTC’s Guidelines for Implementation 39 prohibit tobacco product labelling that is false or misleading, especially labelling that would mislead consumers to believe that the product is less harmful than other products 40 …”
Section: Discussionmentioning
confidence: 99%